KELAS BALITA SEHAT : OPTIMALISASI NAFSU MAKAN ANAK DENGAN TUINA MASSAGE DI BIBIS LUHUR NUSUKAN BANJARSARI SURAKARTA - Eka Deviany Widyawaty; Chusnul Zulaika (Rena Cipta Mandiri, 2026)
Stunting remains a major public health problem in Indonesia, affecting children's physical growth, cognitive development, productivity, and quality of life in adulthood. One of the factors contributing to stunting is poor appetite among toddlers, which leads to inadequate nutritional intake and suboptimal growth. Tuina Massage is a complementary therapy that can help improve digestive function and stimulate children's appetite. This community service program aimed to enhance the knowledge and skills of mothers and Posyandu (Integrated Health Service Post) cadres in applying Tuina Massage as an effort to optimize toddlers' appetite. The program was conducted at Posyandu Bibis Luhur, Nusukan Village, Banjarsari District, Surakarta City, involving 36 toddlers along with their mothers and Posyandu cadres. The intervention consisted of balanced nutrition education, Tuina Massage training and practice sessions, home-based implementation assistance, and growth monitoring of toddlers. The results demonstrated an improvement in participants’ knowledge and skills in performing Tuina Massage. Growth monitoring revealed that the average body weight of toddlers increased from 11.48 kg to 11.75 kg, with an average weight gain of 0.27 kg. A total of 30 toddlers (83.3%) experienced weight gain during the monitoring period. These findings indicate that community empowerment through nutrition education and Tuina Massage training can support improved appetite and growth among toddlers as part of stunting prevention efforts.